2022
DOI: 10.1136/bmjopen-2021-059271
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of tachycardia for mortality in trauma-related haemorrhagic shock: a systematic review and meta-regression

Abstract: ObjectivesHeart rate (HR) is one of the physiological variables in the early assessment of trauma-related haemorrhagic shock, according to Advanced Trauma Life Support (ATLS). However, its efficiency as predictor of mortality is contradicted by several studies. Furthermore, the linear association between HR and the severity of shock and blood loss presented by ATLS is doubtful. This systematic review aims to update current knowledge on the role of HR in the initial haemodynamic assessment of patients who had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 43 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…One review reported that hypocalcemia could potentially be used as an independent predictor of multiple transfusions in trauma and hemostatic resuscitation. [ 48 ] Jávor et al [ 49 ] denied the predictive value of tachycardia for mortality in trauma-related hemorrhagic shock. Other predictors include age, [ 50 ] shock index, [ 51 , 52 ] end-tidal CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…One review reported that hypocalcemia could potentially be used as an independent predictor of multiple transfusions in trauma and hemostatic resuscitation. [ 48 ] Jávor et al [ 49 ] denied the predictive value of tachycardia for mortality in trauma-related hemorrhagic shock. Other predictors include age, [ 50 ] shock index, [ 51 , 52 ] end-tidal CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Although heart rate is a commonly used measure of blood loss, it has been criticized for its lack of specificity and for potentially undermining the concept of permissive hypotension. This is because heart rate can be influenced by many factors other than blood loss, such as anxiety, pain, and medications, making it difficult to accurately assess the extent of blood loss based on this measure alone 49 . Accordingly, in 2021, the RDCR CPGs were revised, mandating systolic blood pressure measurement as a prerequisite for volume administration, with altered consciousness or non‐palpable radial pulse absence serving as alternatives if blood pressure cannot be measured (Figure 3).…”
Section: Defining and Assessing Signs Of Shockmentioning
confidence: 99%
“…Specificity refers to the selectivity of the technique for volume depletion and bleeding. Methods directly examining macro-or microvascular systems received the highest specificity value (3). Hb and Hct also obtained a high specificity score (3) for bleeding [16,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the development of trauma care in the past few decades, roughly 25% of post-injury mortality may be potentially preventable by early detection and proper treatment of life-threatening deteriorations. The further development in the management of hemorrhagic shock (HS) is of utmost importance, since HS can be referred as the main cause of potentially preventable trauma mortality [1][2][3].…”
Section: Introductionmentioning
confidence: 99%